Bowel dysfunction after sigmoid resection for cancer and its impact on quality of life. Issue 1 (13th September 2018) - Elfeki, H; Larsen, H M; Emmertsen, K J; Christensen, P; Youssef, M; Khafagy, W; Omar, W; Laurberg, S
Abstract: Background: Several studies have explored functional outcomes after rectal cancer surgery, but bowel dysfunction after sigmoid resection for cancer has hardly been considered. The aim of this study was to identify the prevalence and pattern of bowel dysfunction after resection for sigmoid cancer, and the impact of bowel function on quality of life (QoL) by comparison with patients who had polypectomy for cancer. Methods: This was a national cross-sectional study. Data were collected from the Danish Colorectal Cancer Group database, and a questionnaire regarding bowel function and European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 QoL questionnaire was sent to all Danish colonic cancer survivors treated with sigmoid resection or polypectomy between 2001 and 2014. Results: A total of 3295 patients (3061 sigmoid resection, 234 polypectomy) responded to the questionnaire (response rate 63·8 per cent). Twelve bowel symptoms were more prevalent after sigmoid resection, including: excessive straining, fragmentation, bloating, nocturnal defaecation, bowel false alarm, liquid stool incontinence, incomplete evacuation and sense of outlet obstruction. QoL impairment owing to bowel symptoms was reported in 16·6 per cent of patients in the resection group and 10·1 per cent after polypectomy ( P = 0·008). Obstructed defaecation symptoms (ODS) were encountered significantly more often after sigmoid resection than following polypectomy (17·9 versus 7·3 per cent; P < 0·001). In the resection group, patients with ODS had substantial impairment on most aspects of QoL assessed by the EORTC QLQ-C30. Conclusion: Sigmoid resection for cancer is associated with an increased risk of long-term bowel dysfunction; obstructed defaecation is prevalent and associated with substantial impairment of QoL. Abstract : Substantial impairment common